Economic Growth Determinants: The Role of Consumption, Investment, Government Spending, and Import-Export - Atong Soekirman (Dinasti Publisher, 2024)
Abstract: The research aims to provide insights into the respective contributions of each factor to overall economic expansion. This article uses qualitative methods with literature from scientific articles as a reference to the results of the research in this article. The researcher provides a perspective on the appropriate literature to support this scientific article as a final result. The study's findings provide valuable insights for policymakers and practitioners who want to drive sustainable economic development. By understanding the complex interplay between different economic variables and their impact on growth, policymakers can design more effective policies aimed at fostering an inclusive and resilient economy. In addition, these findings affirm the importance of ongoing research and analysis to deepen our understanding of the drivers of economic growth and provide a basis for evidence-based policy decisions